Expanding a primary care nurse practitioner fellowship to support rural and underserved pediatric patients in the US - Aaron Carpenter; Catherine Haut; Sarah Wawrzynski; Stacey Bachman; Lisa Kelly (Rural and Remote Health)

(untitled)
Context: A significant shortage of primary care and mental healthcare providers currently exists in the US and is predicted to worsen, emphasizing the imperative for mental health training and collaboration within primary care settings, especially in rural and underserved areas. WHO (2021) has estimated over 18 million health care workers will be needed in rural areas in the US by 2030. It is challenging for primary care providers to work in rural areas of the US due to limited healthcare resources; limited access to emergency, specialty and mental health services; and requirements for skills to manage patients with complex problems. A lack of healthcare professionals specializing in primary care and pediatric care, coupled with rising demand for mental health services in underserved and rural areas, necessitates innovative and sustainable solutions. Nurse practitioners emerge as a key workforce with the potential to provide these comprehensive services, given their adaptability, scope of practice and potential interest in living and working in rural areas. US experiences indicate that these work environments offer increased independent, comprehensive practice opportunities and competitive salaries leading to greater satisfaction and retention.